Islamic Caricature Controversy from Jyllands-Posten to Charlie Hebdo from the Perspective of Arab Opinion Leaders - Kazkaz, Lana (Religions, 2023)
The Jyllands-Posten Muhammad cartoons controversy began after the Danish newspaper Jyllands-Posten published 12 editorial cartoons in September 2005. Cultural and political relations between the West and the Arabic and Islamic worlds have witnessed multiple events that revealed the nature and understanding of historical relations between the worlds, and the role of contemporary media in formulating them. After this incident, the phenomenon of Western media handling of Islamic religious symbols began to arouse interest, where they faced angry responses in the Arabic and Islamic worlds, which denounced Denmark, while Denmark, as a country, refused to apologize to Muslims for what they considered a major abuse, which led some Arab countries to suspend relations with the latter. Additionally, in January 2015, the French magazine Charlie Hebdo was targeted in a deadly attack on its headquarters in Paris, killing 12 people for its “red-line cartoons” on Islam. This study seeks to understand the positions of a group of opinion leaders comprised of intellectuals and influencers who represent cultural and political currents in a number of Arab countries from the phenomenon of cartoons in Western media. This study aimed to evaluate them on the intense reactions of rage witnessed in multiple Islamic countries that occurred after the release of these drawings, and ask them basic questions: Did the Arab media, opinion leaders, and intellectuals have an inciting role that provoked the Western media’s handling of Islamic religious symbols or did this practice coincide with the Arab-Islamic cultural context and its limits? Answering the above questions helped to reveal the features of continuity and change in the perception of opinion leaders in the Arab world on the role of Western media in the dialogue and cultural conflict between the Arab-Islamic and Western worlds.